Groundbreaking ceremony at Perkin-Elmer facility in Meriden, Connecticut - Perkin-Elmer Corporation (1965)
General view of the groundbreaking ceremony for a new Perkin-Elmer Corporation facility in Meriden, Connecticut. Perkin-Elmer President Chester W. Nimitz, Jr. is seen seated at the controls of the machine at the center of the photograph. The other individuals present in the photograph are identified as follows (left to right): Carter H. White (Vice President, Meriden Industrial Development Commission); Meriden Mayor William T. Shea; George D. Huff (Perkin-Elmer official); and Otis C. Ferrell (Perkin-Elmer official). The Perkin-Elmer Corporation was founded in 1937 by Richard Perkin and Charles Elmer as an optical design and consulting company and later expanded into the manufacture of analytical and astronomical instruments.
Keywords: Employees; Perkin-Elmer Corporation; Nimitz, Chester W. (Chester William) Jr., 1915-2002; Corporations